Harnessing the opportunities of austerity: a detailed mapping of the Greek transportation sector - Stamos, Iraklis; Mitsakis, Evangelos; Tsekeris, Theodore (TeMA - Journal of Land Use, Mobility and Environment, 2016)
Since 2009, shortly after the global economic crisis of 2008, Greece has entered into a deep recession phase. The multifaceted presence of austerity is experienced in an increasing number of sectors of the country. The Greek transportation sector is not immune to this state of affairs. The ongoing crisis had a significant impact on its economic (investment, employment, exports-imports turnover) as well as its operational (transportation intensity, throughput, performance) aspects and capabilities. In this paper, a detailed mapping of these impacts is laid out, correlating transport-related characteristics, trends and estimations with the respective economic ones. Specifically, the paper presents analyses of the Greek passenger and freight transportation, following a data-driven approach over several areas. Findings show a substantial decrease of activities overall. Paradoxically, however, austerity can also be said to offer opportunities, such as the development of innovative, cost-effective and outward-looking business schemes, for handling transportation-related issues. In the face of these opportunities, authorities and stakeholders have recently turned their attention to ways of harnessing them as they may arise. The paper conducts a detailed analysis of these efforts to discover prospects for development in the midst of austerity, and highlights the steps currently being taken in that direction.